Strategies to Enhance Health Communication Participation Among Medical Students in Chinese Universities: A Cross-Sectional Study - Jiang N; Chen M; Yan T; Liu Q; Shu Q; Liang X; Tao Z; Nie W; Yang X; Guo Y; Li X; Zhu DJ; et al. (Advances in Medical Education and Practice)
Na Jiang,1,2,* Moxin Chen,1,2,* Tongtong Yan,1,2 Qianwen Liu,1,2 Qin Shu,1,2 Xiaoyi Liang,1,2 Zhuoran Tao,1,2 Wanqin Nie,1,2 Xuefeng Yang,1,2 Yonglin Guo,1,2 Xiaojing Li,1,2 Deyi Jasmine Zhu,3 Yao Fu,1,2 Lin Li1,2 1Department of Ophthalmology, Ninth People’s Hospital, Shanghai Jiao Tong University School of Medicine, Shanghai, People’s Republic of China; 2Shanghai Key Laboratory of Orbital Diseases and Ocular Oncology, Shanghai, People’s Republic of China; 3College of Arts and Science, New York University, New York, NY, USA*These authors contributed equally to this workCorrespondence: Yao Fu, Email fuyao@sjtu.edu.cn Lin Li, Email lin_li@sjtu.edu.cnPurpose: Health communication is the central social process that refers to the systematic dissemination of evidence-based health information to improve public health literacy and promote healthy behaviors. Medical students’ participation in health communication is an effective way to improve public health. This study aimed to explore the current status and influencing factors of medical students’ participation in health communication and offer specific suggestions.Methods: In this cross-sectional study, an online self-designed questionnaire was distributed to medical students during August 2022 to September 2022. Group differences were assessed using the Chi-square test and the Fisher-Freeman-Halton exact test.Results: A total of 314 medical students participated in the survey. The respondents demonstrate a high awareness regarding the importance of health communication. The top two public platforms for students to acquire and disseminate knowledge are WeChat public accounts and short video platforms. 66.56% (209/314) of respondents have participated in health communication. Among undergraduates, the primary barrier to participation is a lack of sufficient professional knowledge and clinical experience (χ 2 = 9.317, P = 0.002). For postgraduate students, a lack of time due to heavy academic load (χ 2 = 11.17, P = 0.001) was the main impediment. Notably, 97.13% of students express a willingness to improve their health communication abilities by participating in activities such as lecture training, studying excellent works and joining clubs or organizations.Conclusion: The respondents agree on the critical role of medical students in disseminating health science knowledge, but their engagement level needs to be improved. Medical students’ health communication ability and participation require collaborative efforts from multiple parties.Keywords: medical students, health communication, health promotion, cross-sectional study